(untitled) (Journal of Hama University, 2022)
This study aimed s to identify the differences between the banks listed on the Damascus parallel stock market by applying the dimensions of Entrepreneurial orientation, This research measured the statistical differences between the study variables according to the personal indicators of the research, The researcher used one way Anova and LSD to study the differences between groups in detail. The study community was represented by the banks listed in the parallel market (Arab Bank, Bank of Syria and the Gulf, Bank of Jordan), and randomized sample laws were relied upon and the sample was distributed to the three banks using proportional distribution The sample size for (The Bank of Syria and the Gulf was 66 questionnaires, Arab Bank 98 questionnaires, Bank of Jordan 75 questionnaires. The study concluded with a number of results: there was a significant difference in risk-taking according to the bank and the highest levels were for the Bank of Syria and the Gulf as it achieved real losses as a result of the risks it faced, followed by Arab Bank and Bank of Jordan. There is significant difference in terms of the dimension of the pro-activeness, as the Bank of Jordan achieved the highest level, while Arab bank, Bank of Syria and the Gulf are equal. There are no significant difference between banks in terms of (autonomy, Customer orientation e and rival- orientation), in addition they are equally able to cope with the current working environment.